On the approximation and growth of entire harmonic functions in $R_n$ - Veselovskaya, O. V. (Ukrains’kyi Matematychnyi Zhurnal, 2018)
We establish a criterion of extendability of harmonic function in a ball of the $n$-dimensional space to harmonic entirefunction and study the growth of entire harmonic function in terms of the best approximation of these function by harmonicpolynomials.